A new generic classification for Thaumatodryininae, Dryininae and Gonatopodinae, with descriptions of new species (Hymenoptera Dryinidae) (Bollettino di zoologia agraria e bachicoltura, 2024)
A new generic classification is proposed for Thaumatodryininae, Dryininae and Gonatopodinae. In the subfamily Dryininae the following new names are proposed in the genus Dryinus: hansonianus, harpax, arimensis, kovariki, parkerianus, ater, australiae, gibbosoides, pseudoafer and dayianus. The following new species of Dryininae are described: Dryinus madagascolus, from Madagascar; Dryinus lini and choui, from Taiwan; Megadryinus pulawskii, from Peru; Dryinus cruciatus, from U.S. Virgin Islands; Dryinus wasbaueri, from Papua. In the subfamily Gonatopodinae the following new names are proposed in the genus Gonatopus: aegypti, fortunatus, tussacensis, owaini, pilosoides, ceballosi, operosus, rufoniger, asiae, insulae, variabilis, americae, cobbenianus, flavoides, stephani, boucekianus. In the same subfamily the following new combinations are proposed: Gonatopus helleni (Raatikainen) and Gonatopus nearcticus (Fenton). The following new species of Gonatopodinae is described: Gonatopus sensitivus, from Madagascar. In the subfamily Anteoninae the following new names are proposed in the genus Anteon: hirashimai, paraflaccum, gauldense. The male of Anteon minimum (Fenton), from the U.S.A., is described. In the subfamily Bocchinae the new species Bocchus rossi, from Western Australia, is described. In the subfamily Apodryininae the male of Apodryinus masneri Olmi, from Chile, is described and the genus Bocchopsis Olmi is considered senior synonym of Australodryinus Olmi. The new name Bocchopsis australis is proposed.
Keywords: taxonomy; Dryinidae